Chiado e Estilo. A importância da noção de Estilo na construção do Chiado de Siza - Andreia Joana Geraldo Couceiro (2018)
This thesis is an interpretive study of Siza's intervention in Lisbon's Chiado district after the 1988 fire. It is developed in the field of design theory, through the formulation of a concrete problem outlined in the title itself: the importance of the notion of Style in the construction of Siza's Chiado. With this aim in mind, the research was based on premises other than those customarily applied in theories relating to interventions in the architectural heritage, since these appeared to lead to a field of specialisation in the discipline that the author did not particularly adhere to, and which was consequently of no immediate interest.In this thesis, History assumes a documentary value, serving as a backdrop for the formulation of a point of view about the Chiado area (before and after Siza).The work is therefore centred upon the process of creation, beginning with an operative reflection that Goethe made about the creation of a work of art, and which, when transposed to the field of architecture, enables us to think about and interpret Siza's intervention in the context of Pombal's Lisbon.As can be seen from the work of José‑Augusto França, the importance of the notion of style does not represent a new approach to understanding the Marquis of Pombal's project for Lisbon's central Baixa district after the earthquake.What this thesis does, however, propose is that we should expand the simple notion of style to encompass a much vaster idea, such as the one proposed by Goethe in a simple imitation of nature, manner and style, putting it to the test in relation to Siza's Chiado.The so‑called "Pombaline style", framed within the history of styles, and Style, in Goethe's (and other similar authors') acceptance of this term, apparently amount to two distinct paths that, in the Pombaline project, and in the interpretation that Siza makes of it, appear to converge with one another.The research that is proposed here seeks to respond to this problematics by invoking the lesson of Siza's Chiado, an exemplary work (in the sense of a benchmark), in which the author seems to develop this same research through the implementation of a design project, or, in other words, through the practice of architecture and its problems.